Symmetry of Tetra-tert-butyltetrahedrane - ASHRAFI, A.R.; GHOLAMI, A. (Asian Journal of Chemistry, 2010)
In this paper, the atom centers of tetra-tert-butyltetrahedrane molecule using the chemistry package HyperChem is calculated followed by the automorphism group of Euclidean graph of this molecule is computed by Gap System.